The Role of Innate Immunity and Bioactive Lipid Mediators in COVID-19 and Influenza - Sahanic, Sabina; Löffler-Ragg, Judith; Tymoszuk, Piotr; Hilbe, Richard; Demetz, Egon; Masanetz, Rebecca K; Theurl, Markus; Holfeld, Johannes; Gollmann-Tepeköylü, Can; Tzankov, Alexandar; Weiss, Guenter; Giera, Martin; et al. (Frontiers in Physiology, 2021)
In this Review, we discuss spatio-temporal kinetics and inflammatory signatures of innate immune cells specifically found in the response to SARS-CoV-2 compared to influenza virus infection. Importantly, we cover the current understanding on the mechanisms by which SARS-CoV-2 may fail to engage a coordinated type I response, and instead may lead to exaggerated inflammation and death. This knowledge is central for the understanding of available data on specialized pro-resolving lipid mediators in severe SARS-CoV-2 infection pointing towards inhibited E-series resolvin synthesis in severe cases. By investigating a publicly available RNA seq database of bronchoalveolar lavage cells from patients affected by COVID-19, we moreover offer insights into the regulation of key enzymes involved in lipid mediator synthesis, critically complementing the current knowledge about the mediator lipidome in severely affected patients. This Review finally discusses different potential approaches to sustain the synthesis of 3-PUFA derived pro-resolving lipid mediators including resolvins and lipoxins, which may critically aid in the prevention of acute lung injury and death from COVID-19.